2015
DOI: 10.1037/lhb0000137
|View full text |Cite
|
Sign up to set email alerts
|

Remorse, psychopathology, and psychopathy among adolescent offenders.

Abstract: Remorse has long been important to the juvenile justice system. However, the nature of this construct has not yet been clearly articulated, and little research has examined its relationships with other theoretically and legally relevant variables. The present study was intended to address these issues by examining relationships among remorse, psychopathology, and psychopathy in a sample of adolescent offenders (N = 97) using the theoretically and empirically established framework of guilt and shame (Tangney & … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 86 publications
(221 reference statements)
1
12
0
Order By: Relevance
“…A study conducted in the USA (N = 270) also noted a relationship between the expression of anger and juveniles in conflict with the law, with teenage offenders reporting anger or the expression of it associated with the avoidance of coping strategies (Eftekhari et al 2004). Such behavior may be related to low levels of guilt, as suggested by the study by Spice et al (2015), which reported on adolescents who had committed crimes for whom guilt was negatively associated with feelings of anger. This implies that the greater the intensity of anger, the lower the feelings of guilt, and hence that crimes committed with intense feelings of anger will be committed with low (or zero) guilt intensity (Spice et al 2015).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…A study conducted in the USA (N = 270) also noted a relationship between the expression of anger and juveniles in conflict with the law, with teenage offenders reporting anger or the expression of it associated with the avoidance of coping strategies (Eftekhari et al 2004). Such behavior may be related to low levels of guilt, as suggested by the study by Spice et al (2015), which reported on adolescents who had committed crimes for whom guilt was negatively associated with feelings of anger. This implies that the greater the intensity of anger, the lower the feelings of guilt, and hence that crimes committed with intense feelings of anger will be committed with low (or zero) guilt intensity (Spice et al 2015).…”
Section: Discussionmentioning
confidence: 93%
“…Such behavior may be related to low levels of guilt, as suggested by the study by Spice et al (2015), which reported on adolescents who had committed crimes for whom guilt was negatively associated with feelings of anger. This implies that the greater the intensity of anger, the lower the feelings of guilt, and hence that crimes committed with intense feelings of anger will be committed with low (or zero) guilt intensity (Spice et al 2015).…”
Section: Discussionmentioning
confidence: 96%
“…and being put on the spot (M FA SOTP 13) This discomfort for both parties may be due to instinctively wanting to avoid group members feeling shame or guilt. Research has indicated a clear link between shame and the tendency to externalize blame and anger (Harper & Arias, 2004;Harper & Arias, 2004;Harper & Arias, 2004;Paulhus, Robins, Trzesniewski, & Tracy, 2004), and between guilt and anger, depression and anxiety (Spice, Viljoen, Douglas, & Hart, 2015). In a group format, these responses to shame or guilt may only be exacerbated and prevent the group members from engaging.…”
Section: Think Other Guys Don't Particularly Like Having To Think Amentioning
confidence: 99%
“…Tangney, Stuewig, Mashek, and Hastings () found that among 550 jail inmates there were differences between those reporting shame and guilt. Shame is usually associated developmentally with harsh parental judgments about the child, not the behavior, and it does not map onto moral competence, in part because of its self‐focus, defensiveness, and likely association with more emotional disturbance (Bohart & Stipek, ; Spice, Viljoen, Douglas, & Hart, ; Tangney et al, ).…”
Section: Moral Competencementioning
confidence: 99%